Inovasi Pembelajaran Daring Dalam Penerapan Merdeka Belajar Perguruan Tinggi di Masa Pandemi Covid-19 (Tinjauan Literatur) - Gamal Muhammad Rizka (FKIP Universitas Lampung, 2021)
The world of education is now entering an adjustment phase in the teaching and learning process during the Covid-19 pandemic. Limited learning conditions online between lecturers and students, overcome by the campus by preparing to develop policies and strategic steps so that the process of sharing activities of lecture topic materials continues to run using E-learning application facilities. To ensure that learning can generate creativity, critical power, and be able to make students independent is certainly not an easy matter. The flexibility of lecturers in developing learning innovations in order to attract students to continue to be excited is something worth noting. With the policy of freedom of learning, it is expected to provide flexibility to students to study off campus while still accompanied by lecturers, in order to still realize an ideal education. current pandemic conditions. The method used is a review of literature studies with a descriptive approach. The purpose of writing this article is to know that the creativity of lecturers and students is highly expected, so that in the process of online learning, this innovative learning model is useful to produce the quality of student learning and also realize an independent learning program. The result of writing this article is that even if we are in a state of pandemic covid-19, it is expected that all education implementers can apply the concept of freedom of learning so that they can explore creativity, innovate and continue to find solutions to challenges in online learning.Keywords: Covid 19, Learning Innovation, Merdeka Belajar